Improved Acuity and Dexterity but Unchanged Touch and Pain Thresholds following Repetitive Sensory Stimulation of the Fingers - Rebecca Kowalewski; Jan-Christoph Kattenstroth; Tobias Kalisch; Hubert R. Dinse (Neural Plasticity)
Neuroplasticity underlies the brain’s ability to alter perception and behavior through training, practice, or simply exposure to sensory stimulation. Improvement of tactile discrimination has been repeatedly demonstrated after repetitive sensory stimulation (rSS) of the fingers; however, it remains unknown if such protocols also affect hand dexterity or pain thresholds. We therefore stimulated the thumb and index finger of young adults to investigate, besides testing tactile discrimination, the impact of rSS on dexterity, pain, and touch thresholds. We observed an improvement in the pegboard task where subjects used the thumb and index finger only. Accordingly, stimulating 2 fingers simultaneously potentiates the efficacy of rSS. In fact, we observed a higher gain of discrimination performance as compared to a single-finger rSS. In contrast, pain and touch thresholds remained unaffected. Our data suggest that selecting particular fingers modulates the efficacy of rSS, thereby affecting processes controlling sensorimotor integration.